Correlate Factor With Teenage Pregnancy - Yunitasari, Eva; Marliyana, Marliyana; Suharti, Sri; Novita, Dian (Universitas Aisyah Pringsewu, 2024)
Teenage pregnancy is a pregnancy that occurs when a teenager is 20 years old. Women who become pregnant at the age of 15-19 years have a greater risk of suffering complications from pregnancy and childbirth. Teenage pregnancy can have an impact on the future of the teenager herself, the child she is carrying, and her family. Apart from that, the impacts that arise due to early pregnancy are not only caused by habits, peers, and the teenager's environment but are also caused by the teenager's own knowledge. The research objective is to determine the correlated factors with teenage pregnancy in the working area of the Gadingrejo Public Health Center in Pringsewu. This research used a cross-sectional design with a sampling technique using purposive sampling. The number of samples used was 287 female teenage respondents. Test the analysis using the Chi-Square test.The results of the analysis show that all factors are significantly correlate to teenage pregnancy. Namely, there is a correlation between knowledge and teenage pregnancy (p=0.031), there is a correlation between the role of parents and teenage pregnancy (p=0.002), there is a correlation between attitudes and teenage pregnancy (p=0.041) and there is a not correlation between the role of peers and teenage pregnancy at the work area of Gadingrejo Public Health Center in Pringsewu (p=0.053). It is expected that health care workers can prioritize health promotion in schools (middle and high schools) to increase teenagers' knowledge about the impact of teenage pregnancy, or can choose cadres/persons responsible for teenagers reproductive health in each school.